2021
DOI: 10.1097/pcc.0000000000002835
|View full text |Cite
|
Sign up to set email alerts
|

Prediction Model Performance With Different Imputation Strategies: A Simulation Study Using a North American ICU Registry

Abstract: To evaluate the performance of pragmatic imputation approaches when estimating model coefficients using datasets with varying degrees of data missingness. DESIGN:Performance in predicting observed mortality in a registry dataset was evaluated using simulations of two simple logistic regression models with agespecific criteria for abnormal vital signs (mentation, systolic blood pressure, respiratory rate, WBC count, heart rate, and temperature). Starting with a dataset with complete information, increasing degr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 46 publications
0
4
0
Order By: Relevance
“…We also performed and reported the performance measure from a complete-case analysis. Even though the results of the complete-case analysis were different from those of the MICE approaches, we believe this finding had no strong clinical implication, as a growing body of evidence has found that complete-case analysis often leads to errors, result misinterpretations, and impaired generalizability [ 28 ]. Second, a large proportion of eligible patients were excluded due to incomplete or unverifiable data on relevant dates.…”
Section: Discussionmentioning
confidence: 94%
“…We also performed and reported the performance measure from a complete-case analysis. Even though the results of the complete-case analysis were different from those of the MICE approaches, we believe this finding had no strong clinical implication, as a growing body of evidence has found that complete-case analysis often leads to errors, result misinterpretations, and impaired generalizability [ 28 ]. Second, a large proportion of eligible patients were excluded due to incomplete or unverifiable data on relevant dates.…”
Section: Discussionmentioning
confidence: 94%
“…Dealing with missing data Multiple imputation methods were undertaken to estimate missing data over 50 iterations to generate 20 complete datasets for model development [33]. To determine whether imputation led to radically different results, a sensitivity analysis was performed by comparing the outcomes of the imputed data set with complete cases only.…”
Section: Discussionmentioning
confidence: 99%
“…32 Data were assumed to be missing at random and potential predictors of missing variables were included for imputation. 33,34 Convergence and observed versus imputed value plots were visually checked for quality control. 32 A penalized linear regression method, least absolute shrinkage and selection operator (LASSO), was used for variable selection.…”
Section: Discussionmentioning
confidence: 99%
“…32 Data were assumed to be missing at random and potential predictors of missing variables were included for imputation. 33 34 Convergence and observed versus imputed value plots were visually checked for quality control. 32…”
Section: Methodsmentioning
confidence: 99%